Culture in Nepal: An Exploration of the Legacy and its Way Forward - Siwakoti, Mamta; Adhikari, Sanjay (Kathmandu School of Law Review, 2018)
“I do not think we would conquer this country, unless we break the very backbone of this nation, which is her spiritual and cultural heritage, and therefore, I propose that we replace her old and ancient education system, her culture, for if the Indians think that all that is foreign and English is good and greater than their own, they will lose their self-esteem, their native culture and they will become what we want them, a truly dominated nation.” Thomas Babington Macaulay This paper quotes the ever-controversial Thomas Babington Macaulay at the outset because it seems we have long forgotten the gravity our roots hold. It is, now, imperative that we, the Nepali people realize the gold mine we are sitting on, our unique identity and the heritage associated with it. We have already lost a lot; some in the name of development and some in the crevices of time. Our languages, education system, music, food, buildings, settlements, the uniqueness and practices which are associated with our civilization are the ones that set us apart from the world. While the researchers wholeheartedly agree that certain practices such as Sati, Chaupadi, Deuki, Jhuma were indeed violations of inherent human rights in the name of customs, culture and practices and had to be eradicated, we also equally raise voices for those aspects of our culture that we can celebrate, namely our cultural heritage. Now maybe the right time to decide what we want in the form of development? Another copy of a Western City or a Nepal that is unique in all its rights, a Nepal where road expansion is not synonyms to development, where speaking English is not the yardstick for assessing education and where we make our own rules for development. This paper aims to raise questions regarding the said issues. This paper is based on the doctrines related to cultural heritage in Nepal. The researchers carried out on-site surveillance but owing to the lack of technical expertise in the field, the researchers have based their conclusions and recommendations mainly on the reports of Department of Archaeology, experts in the field of cultural heritage in Nepal and government documents depicting the scenario of heritage in Nepal, pre and post the 2015 earthquake.DOI: https://doi.org/10.46985/jms.v6i2.211